A theory evaluation of a peer education programme. - Naude, Zani (Institute for Monitoring and Evaluation, 2024)
Peer education is a popular strategy to promote positive behaviour among youths. Peer education programmes are usually influenced by either the cognitive behaviour or the structural approach. The cognitive behaviour approach views behaviour change as an individualistic decision that is influenced by an individual's knowledge of the causes and consequences of risk behaviour. The structural approach in contrast rejects the idea that behaviour is an individual decision instead arguing that decision-making takes place within the context of socio-economic dynamics and social and cultural norms. The approach that an organisation favours will influence the design of the programme. Mfesane implemented a peer education programme in the Saldanha Bay Municipality in 2008. This programme was rooted in the Cognitive Behaviour Approach and was targeted at Grade 9 to Grade 12 learners in various high schools in the Saldanha bay area. The programme aimed to convey knowledge of HIV/AIDS to the youth in order to change the youth's sexual behaviours and thus reduce the prevalence of HIV/AIDS. An outcome evaluation that was conducted at the end of the programme's 3 year span found that although the programme successfully increased the youth's knowledge of HIV/AIDS, it did not succeed in changing risk behaviour due to the fact that more than half of the youths were already sexually active by age 16. The evaluation findings motivated Mfesane to review its peer education programme. Initially the organisation considered presenting the programme to a younger cohort. However, the current legal framework in South Africa would restrict what messages Mfesane could share with a younger audience. Instead the organisation agreed to continue targeting high school learners, but to reformulate the programme in order to improve the impact of the programme. The evaluator was approached to conduct a theory evaluation that would assist Mfesane to formulate a more effective programme. A theory evaluation extracts programme assumptions from stakeholders in order to assess the plausibility thereof based on social science literature and previous evaluation findings. During the planning phase of a new programme a theory evaluation can be used to ensure that stakeholders have a common view of the programme and the programme can plausibly achieve its desired outcomes. This theory evaluation was guided by three specific questions: 1) what are the underlying assumptions of the programme; 2) are the assumptions based on clear theoretical linkages; and 3) does evidence exist to support the programme assumptions? These questions guided the systematic method that was used to gather the information that informed the recommended programme theory. The programme assumptions were elicited from programme staff through individual interviews and two focus groups' discussions; one with the programme implementers and another with the programme managers. The separate focus group discussions enabled the evaluator to adopt strategies suited to the group's level of experience and previous exposure to programme theory. The programme implementers were systematically introduced to the different concepts used in programme theory before constructing a common programme theory while the programme managers could directly formulate a programme theory. In structuring their programme theories, both groups moved away from the cognitive behaviour approach and adopted a more holistic approach towards behaviour change that resembles the structural approach. An interesting finding was that in both instances the groups also moved away from focussing on risk prevention rather proposing to strengthen youth to become successful adults. However, the two groups proposed significantly different programme theories and in neither instance did these theories have strong causal links. After reviewing both programme theories, the evaluator presented the two groups with the programme outcomes that had been identified uniquely by each group and those that overlapped. This was used by Mfesane as a guide to identify the outcomes it would like to achieve through the new programme. Although the proposed programme theories supplemented the peer education programme with additional interventions such as income generation, in the end, the organisation for practical reasons decided to continue focusing primarily on peer education as an intervention. The evaluator assessed the plausibility of the proposed new peer education programme by interrogating social science literature and previous evaluation findings. A proposed causal chain for behaviour change was identified by integrating two behaviour change theories, the Social Cognitive Theory and the Theory of Planned Behaviour, into a single model. This model was used to measure how effectively the proposed activities could facilitate behaviour change. Based on these findings the evaluator could recommend a plausible programme theory in line with Mfesane's vision for the peer education programme. The differences between the two programme theories illustrated the value of a programme theory evaluation during the planning phases to ensure that stakeholders start the programme off with a common understanding thereof.